On the effect of Fe（Ⅲ） on proliferation of Microcystis aeruginosa at high nitrate and low chlorophyll condition - Rong Chen Zhen Lei Jiayuan Ji Xiaochang Wang Yu-You Li Yuan Yang Lu Zhang Tao Xue (环境科学学报：英文版, 2017)
The impact of Fe concentrations on the growth of Microcystis aeruginosa in aquatic systems under high nitrate and low chlorophyll conditions was studied. The responses of cell density,total and cell chlorophyll-a intracellular Fe content and organic elemental composition of M.aeruginosa to different concentration gradients of Fe（Ⅲ） in the solutions were analysed. The results showed that the proliferation speeds of M. aeruginosa were：（1） decelerated when the Fe（Ⅲ） concentration was lower than 50 μg/L in the solutions,（2） promoted and positively related to the increase of Fe（Ⅲ） concentration from 100 to 500 μg/L in the solutions over the experimental period, and（3） promoted in the early stage but decelerated in later stages by excess adsorption of Fe by cells when the Fe（Ⅲ） concentration was higher than 500 μg/L in the solutions. The maximum cell density, total and cell chlorophyll-a were all observed at 500 μg Fe（Ⅲ）/L concentration. The organic elemental composition of M. aeruginosa was also affected by the concentration of Fe（Ⅲ） in the solutions, and the molecular formula of M. aeruginosa should be expressed as C7–7.5H14O0.8–1.3N3.5–5according to the functions for different Fe（Ⅲ）concentrations. Cell carbon and oxygen content appeared to increase slightly, while cell nitrogen content appeared to decrease as Fe（Ⅲ） concentrations increased from 100 to 500 μg/L in the solutions. This was attributed to the competition of photosynthesis and nitrogen adsorption under varying cell Fe content.